Einige Artefakte für die Königin Ti-Aa aus Sakkara. - Osman, Ahmed M. (Abgadyat, 2026)
Through the discovery of several important archaeological artifacts in the excavations of the University of Science and Technology at Tabet Al-Geish, this research sheds light on how King Tuthmosis IV attempted to elevate his motherʼs status and raise her to the level of the great queens, even though she was only the concubine of King Amenhotep II. Tuthmosis IV had a temple built for the goddess Hathor to honor the memory of his mother, Queen Ti-Aa. He granted her royal titles and allowed her to inscribe her name on a royal cartouche, as was reserved for the great queens. She received the title of King Consort and Queen Mother, the title of Great Royal Consort at the temple, and other important titles that gave her a prominent position during the reign of her son Tuthmosis IV. She had not enjoyed this position during the lifetime of her husband, King Amenhotep II, as he had not allowed her to inscribe her name on a royal cartouche. Here, we will examine some of the archaeological finds from Tabet Al-Geish to the east, which include depictions and inscriptions of Queen Ti-Aa.